Identifying the Behavioral Intent to Use Social Media through the application of UTAUT in ANR and Turfgrass Extension - Barbara Worley; Jason Peake; Nicholas E. Fuhrman (Journal of Applied Communications, 2023)
Little research exists on the role Extension Agricultural and Natural Resources professionals play in communicating information about new turfgrass cultivars. In an effort to analyze behavioral intentions related to social media and its use in the turfgrass industry, the researchers drew from the unified theory of acceptance and use of technology (UTAUT). A pilot instrument was developed to measure the intent of University researchers and county-based Extension professionals to use social media to disseminate turfgrass information, as well as their use of social media for seeking turfgrass information. This case study examined the role of county-based ANR Extension professionals across six states, analyzing their role as either creators or disseminators of ANR and turfgrass information, their intent to use social media, and their use of these communications to engage with ANR and turfgrass information. Findings of this study show that Facebook is the primary communications channel used by county-based Extension professionals. Further, it has been determined that the role of the county-based Extension professional in “creating” verses “using” previously established research-based information to disseminate to clientele is not well-defined. Broader implications include examination of performance expectations of county-based personnel related to their use of social media for communicating turfgrass information.
Keywords: communication; agriculture and natural resources; Extension Agent; behavioral intent; turfgrass